Online Home Visitation as Parents’ Assistance in Supporting Children’s Learning: A Covid-19 Case Study - Selesiana, Clara; Kalauserang, Esther Deborah (International Journal of Educational Review, 2024)
As the Covid-19 new normal causes online learning to be implemented in Indonesian schools where parents function as the child’s primary educator at home, the aim of this research is to examine the benefit of online home visitation amidst the pandemic and how teachers can assist parents to support their children’s learning through online home visitation experiment. This research employs qualitative method and case study to examine personal experience of the subject, involving a teacher and a single parent of student X from Sekolah Dasar Teologi Kristen Jogja Patriae Academy; the mediums used are online meeting platform (Google Meet) and interview guidelines. Results show the parent of student X could evaluate her child’s progress and discover new points of view from the teacher. Meanwhile, the teacher could understand the parent’s struggle in educating the child through utilizing school values as common ground, exchanging views of the child/student development and providing solutions for parents. Insights of this research remain relevant and applicable for today’s post-Covid19 hybrid education, particularly for schools that are looking for ways for teachers in supporting parents to maintain the child’s academic performance or how parents and teachers can keep up with the child’s current condition by exchanging perspectives with one another. Although there are myriads of papers on teacher’s online home visitation during the pandemic, this research highlights one of the important components of the result that school values play a big role as a common ground to shape both teacher-parent perspectives on the student’s education during the pandemic.